Persepsi Orang Tua tentang Peran Pendidikan Jasmani dalam Pengembangan Keterampilan Motorik Anak Usia Dini di Taman Kanak-Kanak PGRI Desa Samba Bakumpai - Juwita, Dewi Ratna; Syarif, Akhmad; Saputra, Khairunnisa (INTELEKTIUM, 2025)
This study aims to describe and explore in depth the perceptions, views, and beliefs of parents of students at the PGRI Kindergarten in Samba Bakumpai Village regarding the role or contribution of physical education in optimising the development of their children's gross and fine motor skills at an early age. The method used is a qualitative approach, involving in-depth interviews with parents of children aged 3-6 years at PGRI Kindergarten in Samba Bakumpai Village. The findings of this study confirm that parents generally recognise the importance of physical activities that can develop motor skills in young children. However, their perceptions of the specific role of physical education in developing structured motor skills still need to be improved. Parents' understanding of physical education in children's motor development indicates the need for more intensive socialisation from the school/early childhood education institution to parents. Explanations regarding the objectives of the physical education curriculum, the types of motor skills developed, and how parents can support them at home would be highly beneficial. Additionally, collaboration between schools and families is crucial. Schools can provide suggestions for simple physical activities that can be done at home, while parents can create an environment that supports children's movement.